Morphological and structural investigation of SrWO4 microcrystals in relationship with the electrical impedance properties. Issue 34 (2nd August 2017) - Dirany, Nadine; McRae, Edward; Arab, Madjid
Abstract : Synthesis of SrWO4 crystal with spindles and spheres morphologies at ambient temperature. A structuring in tetragonal scheelite favors mixed conduction properties based on order–disorder transition. Abstract : In this paper, strontium tungstate (SrWO4 ) microcrystals have been synthesized at room temperature using a wet chemical method, without any surfactant or template, by adjustment of the precursor concentration and pH solution. The developed mineralization process allows obtaining homogeneous structures with controlled morphologies, including spindles and spheres. Scanning electron microscopy, X-ray diffraction combined with Rietveld analyses and Raman spectroscopy, are used to characterize the detailed scheelite-type tetragonal structures and morphologies and to highlight the size and microstrain effects. In addition to the Raman bands characteristic of the scheelite phase, it was found a strong low frequency modes assigned to high distortion of the SrO8 polyhedra. The mechanisms underlying growth and shape evolution are proposed taking into account the effects of precursor concentration and thermal treatment on the stability of the different morphologies which have been investigated in detail. Electrical conduction analyses have been carried out as a function of temperature in both AC and DC current modes. The results are interpreted in terms of a Nyquist representation, such that the spindles show a single semicircle at high frequencies, while a second semicircle appears at lower frequencies for the spheres. The measured conductivities have similar electrical transitions. Below 500 °C, the conductivity is mainly due to electron charge carriers; however above this temperature, the conductivity becomes mixt due to the order–disorder transition. Moreover, the associated activation energies of the spheres are higher than those of the spindles.